Implementation Scheme Techniques in Improvement Understanding Ability in Reading - Muhammad Hifdil Islam (LP3M Universitas Islam Zainul Hasan Genggong, 2016)
Class Action Research aims to improve reading comprehension skills through the application of engineering scheme on MA students. Darut Tauhid Tanjungsari Krejengan. This study was conducted on 40 students MA. Darut Tauhid Tanjungsari Krejengan Probolinggo of the total amount to 78 students. Data collected malalui observation of teachers, students and study notes. The results showed the average value before the action research by 50%, and the average value of 73% after the action. This shows an increase in students’ reading comprehension skills MA. Darut Tauhid by 23%.